Vernacular rural heritage in Turkey: an intuitional overview for a new living experience - Hasgül, Esin; Olgun, İnci; Karakoç, Erhan (Emerald, 2021)
PurposeThe purpose of this paper is to emphasize passive energy refurbishment of vernacular building heritages and propose new application principles of sustainability from these vernacular heritages into contemporary architecture.Design/methodology/approachThis paper is based on a research project (The Creation of a Prototype Project within the Application of Traditional Methods in Kastamonu, Küre Rural Settlements, 2017), through which vernacular architecture examples were analyzed, projecting for future interpretations for rural environments. Defining vernacular rural design principles is centrally important for the purposes of this project. As a case study from the Black Sea Region in Turkey, this example is investigated, and the outcomes of the analysis are used to reproduce in contemporary architectural terms the energy efficiency and rural patterns of the flexible rural house experience.FindingsThe research provides design principles for developing a new living experience in rural environments. The overall planning and architectural analysis are made in five neighborhoods in Küre, and three of unique vernacular architecture examples are chosen according to several criteria defined in “Kastamonu-Küre Ersizlerdere Village Design Guideline Project, 2014” to get the optimum data. Materials, orientation, form, spatial organization and building's indoor-outdoor relationship were analyzed by Autodesk's “Ecotect Analysis” simulation program.Practical implicationsResults of the proposed design principles of rural housing will be useful for new housing interpretations related to better rural development.Originality/valueWhile defining energy efficiency criteria of vernacular itself, the results of this paper suggest new local solutions to ecological building design and engage with critical regionalism principles referring to the potentials of what traditional dwellings can teach contemporary design.
Keywords: Rural Guideline; Rural House; Building Heritage; Vernacular; Design Principles; Passive Energy